Mendapatkan Algoritma Menghitung Koefisien-koefisien Persamaan Regresi Linear Dua Variabel untuk Dikoding ke dalam Bahasa Pemrograman - Anwar Ramli (Jurnal Peluang, 2012)
AbstractData in research usually are provided in discrete value. Many researchers want to predict the value of the discrete values. The strategy is to find the simple function that appropriates of the value. One of the ways that is used is least square method that is linear regression. This paper aims to describe to readers about how to find the algorithm of counting the coefficient a and b of linear regression  y = a + bx for coding to programming language. Keynotes: linear regression, algorithm, programming language.